Pengaruh Mindful Parenting dalam Menurunkan Stres Pengasuhan: Tinjauan Sistematik - Nazlah Hasni; Diah Karmiyati (Universitas Negeri Malang, 2023)
Having children and becoming parents is the dream of most couples. Children are a gift, the apple of one's eye, a soulmate, and a source of hope. However, on the other hand, without denying the gratitude, it is undeniable that raising children is a significant task with all the complexities that follow. Without proper knowledge, the process of raising children can bring about pressure that can lead to stress. Certainly, this stress can have a negative impact on the well-being of parents and the growth of children. Mindful parenting is an awareness-based approach. Simply put, the main motivation of this approach is to enhance parents' abilities to fulfill their roles as primary caregivers and educators, both in terms of mind, emotions, and responses to their children. This systematic review aims to determine the influence of mindful parenting as an effective approach to dealing with parental stress in Indonesia. The method used is a literature review, where articles were obtained through the collection from the Publish and Perish 8 database of Google Scholar using inclusion and exclusion criteria. Keywords used in literature search include